2020
DOI: 10.1177/1099800420941094
|View full text |Cite
|
Sign up to set email alerts
|

Association of Depressive Symptoms with Perceived Stress and Proinflammatory Cytokines in Treatment-Naïve Patients with Breast Cancer

Abstract: Objectives: This study aimed to explore the levels and associations among depressive symptoms, perceived stress, and proinflammatory cytokines (interleukin-1β, interleukin-6, and tumor necrosis factor-α) in treatment-naïve patients with breast cancer. Methods: A cross-sectional study with one case and two control groups. Patients with breast cancer, matched patients with depression, and matched healthy women completed questionnaires and blood collection between May 2015 and March 2017. Data were analyzed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In addition, in the younger cohort in the All Low class, higher levels of depressive symptoms were associated with higher levels of the anti-inflammatory cytokine, IL-10. Similarly, a recent study found a negative correlation between the pro-inflammatory cytokine, IL-1β, and depressive symptoms in patients with breast cancer with a mean age of 45 years ( Li et al, 2021 ). In another study, higher levels of depressive symptoms were associated with higher levels of IL-1β, and TNF-α post-surgery in breast cancer patients with a mean age of 50 years ( Bouchard et al, 2016 ).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, in the younger cohort in the All Low class, higher levels of depressive symptoms were associated with higher levels of the anti-inflammatory cytokine, IL-10. Similarly, a recent study found a negative correlation between the pro-inflammatory cytokine, IL-1β, and depressive symptoms in patients with breast cancer with a mean age of 45 years ( Li et al, 2021 ). In another study, higher levels of depressive symptoms were associated with higher levels of IL-1β, and TNF-α post-surgery in breast cancer patients with a mean age of 50 years ( Bouchard et al, 2016 ).…”
Section: Discussionmentioning
confidence: 79%
“…In another study, higher levels of depressive symptoms were associated with higher levels of IL-1β, and TNF-α post-surgery in breast cancer patients with a mean age of 50 years ( Bouchard et al, 2016 ). While the findings in the literature are inconsistent, previous studies ( Bouchard et al, 2016 ; Li et al, 2021 ) included patients with a wide age range and did not dichotomize the sample into older and younger cohorts. Our findings suggest a pro-inflammatory role in depressive symptoms among the older cohort compared to the younger cohort that is likely related to aging and cancer immune modulations.…”
Section: Discussionmentioning
confidence: 99%
“…Proin ammatory cytokines such as IL-1β and TNF-α show overall upregulation in depression, which suggests that immune activation is present. Indeed, the relationship between these proin ammatory cytokines and depression among patients with breast cancer has been con rmed by many researchers [31,32]. IL-1β and TNF-α are generated by monocytes, and can induce MSCs to differentiate into in ammatory CAFs that promote the metastasis of breast tumor cells [33].…”
Section: Discussionmentioning
confidence: 99%